Simplified channel authentication algorithm for secure quantum key distribution - Elwadeya, Mohamed Youssef Khalaf; Al-Khateeb, Khalid A. Saeed; Hasbullah, Nurul Fadzlin (2014)
Quantum key distribution (QKD) is characterized by the implementation of the principles of quantum mechanics in distributing the symmetric cryptographic key between two communicating stations. The quantum channel through which a light beam travels and then examined quantum-mechanically is governed by several quantum cryptographic protocols. This paper presents a simplified algorithm of the quantum authentication process (QAP) of the six-state deterministic quantum protocol (6DP). The proposed setup replaces the nonlinear crystal BBO which is responsible for the second harmonic generation process with a simple polarization splitting using Glan Thompson Polarizer (GTP).